Da indústria ao design utópico dos Fab Labs: uma análise de experiências na cidade de São Paulo - MONEZI, Elton Reis (2018)
This research investigates the meaning of industrial production as a counterpoint to the emerging proposal of digital manufacturing contemporary model, which includes the Maker culture and its admissible interference in the materialization of goods and its relationship with design, industry and consumer. It aims to evaluate the relevance of Fabrication Laboratories (Fab Labs), in the city of São Paulo, as being auspicious environments to disruptive innovation and entrepreneurship, in the productive and social insertion scenario. There is a practical demand into Fab Labs, where visitors are allowed to build elements without prior design knowledge or drawing software. The method adopted in the research is qualitative and includes a data survey through interviews with the heads of four laboratories selected in the city of São Paulo, and, subsequently, the critical analysis of the data is made. It is questioned if the culture of manufacture would cause substantial mutations in a capitalist system and what would be the most appropriate practice to society.